Genetic model of motor neuron disease in B6SJL-Tg mice: new data on the dynamics of motor symptoms and immunohistochemical manifestations of the neurodegenerative process - А. V. Stavrovskaya; D. N. Voronkov; E. A. Artyomova; B. V. Belugin; М. М. Shmarov; N. G. Yamshchikova; А. S. Gushchina; А. S. Olshansky; B. S. Naroditskiy; S. N. Illarioshkin (Нервно-мышечные болезни)
Introduction. Over the past several decades, the study of mutations associated with motor neuron disease has led to the development of a number of transgenic animal models of motor neuron disease. One of the causes of the familial form of this disorder is mutations in the gene encoding Cu/Zn superoxide dismutase 1. The B6SJL-Tg (SOD1*G93A) mouse strain expresses a mutant form of human superoxide dismutase 1. Aim of study. To assess motor functions, dynamics of survival, and morphological changes in the spinal cord of transgenic B6SJL-Tg (SOD1*G93A) mice. Material and methods. In total, 31 animals have been studied. Starting from the age of 22 weeks, once every two weeks, the “open field” and “beam walking” motor tests were performed. The morphological changes in the spinal cord were evaluated at intermediate (26–35 weeks) and late stages (40–45 weeks). Neuronal proteins NeuN and PGP9.5, gliofibrillar protein, cyclonucleotide phosphatase (a marker of oligodendroglia) and a marker protein of microglia IBA1 were detected by immunohistochemistry; antibodies MTC02 to the outer membrane protein were used to detect mitochondria. Results. Motor problems appeared at the age of 24–26 weeks and steadily progressed; one could see consistent paresis of the hindlimbs, then the forelimbs, which was accompanied by general hypotrophy of the animals. There was a greater variability in the timing of symptom onset and life expectancy in males compared to females. The neurodegenerative process with damage to motor neurons was accompanied by the activation of micro- and astroglia. A sharp decrease in immunoreactivity to the mitochondrial marker MTC02 was found. Conclusion. The obtained results demonstrate new details of the development of a complex of motor and pathomorphological changes characteristic of motor neuron disease in B6SJL-Tg (SOD1*G93A) mice. Clarification of the fine dynamics of the neurodegenerative process in these animals is of great importance for monitoring the course of the disease during preclinical trials of new drugs and methods of gene therapy.